1991
DOI: 10.1002/gcc.2870030409
|View full text |Cite
|
Sign up to set email alerts
|

Detection and analysis of origin of i(12p), a diagnostic marker of human male germ cell tumors, by fluorescence in situ hybridization

Abstract: The i(12p) chromosome marker has been shown to be a diagnostic and prognostic marker of human male germ cell tumors (GCTs). An analysis of the i(12p) and chromosome 12 aneuploidy was performed in five primary cell cultures and three established cell lines derived from human male GCTs by fluorescence in situ hybridization (FISH) with a chromosome 12 centromere-specific alpha-satellite DNA probe. Distinct differences in the centromeric signals originating from the i(12p) and normal chromosome 12 were detected, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 22 publications
1
26
1
1
Order By: Relevance
“…It has been known for more than a decade that the majority of TGCTs contains one or more isochromosomes of the short arm of chromosome 12 (Mukherjee et al, 1991;Rodriquez et al, 1993a;Van Echten et al, 1995;Mostert et al, 1996b). Moreover, it has been demonstrated, that TGCTs without i(12p) also show over-representation of 12p-sequences (Suijkerbuijk et al, 1993;Rodriquez et al, 1993b;Smolarek et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known for more than a decade that the majority of TGCTs contains one or more isochromosomes of the short arm of chromosome 12 (Mukherjee et al, 1991;Rodriquez et al, 1993a;Van Echten et al, 1995;Mostert et al, 1996b). Moreover, it has been demonstrated, that TGCTs without i(12p) also show over-representation of 12p-sequences (Suijkerbuijk et al, 1993;Rodriquez et al, 1993b;Smolarek et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the presence of the cyclin D2 in NS depends on the histology (Houldsworth et al, 1997) is neutral with respect to the hypothesis that cyclin D2 is the gene of interest. Overrepresentation of the cyclin D2 gene in most of the TGCTs and derived cell lines (Sicinski et al, 1996) probably merely re¯ects the over-representation of the complete short arm of chromosome 12 found in virtually all TGCTs (Mukherjee et al, 1991;Rodriquez et al, 1993a,b;Van Echten et al, 1995;Mostert et al, 1996b). A number of other genes previously proposed as candidates we also considered less likely because they map outside the SROA (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The size of the centromere signals for chromosome 12 was variable and their copy numbers generally high. This was attributed to the presence of the i(12p) chromosome, although it is not possible to predict in individual cases whether the rearrangement producing this chromosome results in a larger or smaller centromeric signal than that found in the normal chromosome 12 (Mukherjee et al, 1991). The results from the analysis of the copy number of the PACs from the lp32 and lp35 region in relation to the pericentromeric probe for chromosome 1 for cases 33, 44, 36 and 39 showed loss of the region, consistent with the CGH analysis.…”
Section: Interphase Fish Analysismentioning
confidence: 99%
“…This technique confirmed the genuine nature of the i(12p) in TGCT [18,19] and showed that all i(12p)-negative TGCT tested so far contained additional 12p sequences [13,20], implying that relative overrepre sentation of 12p sequences is crucial for the development of a clinically manifest TGCT. FISH on interphase nuclei with a centromere-specific probe for chromosome 12 has been used to identify TGCT [11,21], based on a consistent size difference between the hybridizing centromeric region of the isochromosome and the normal chromosome 12 homologues. The reliability of this method depends on the consistent involvement of centromeric sequences in the formation of i[12p).…”
Section: Introductionmentioning
confidence: 99%